Efficacy and risk factors of stent placement in the treatment of malignant tracheoesophageal fistula - Wang, Qingxia; Duan, Zhihong; Liu, Shiqi; Shi, Ruihua (Frontiers in Oncology, 2024)
Background: Due to the low incidence of malignant tracheoesophageal fistula and the paucity of relevant clinical studies, the benefits of stent implantation have not been well documented. It remains unclear which factors may affect fistula closure.Methods: Between January 2015 and January 2021, 344 patients who were diagnosed with malignant tracheoesophageal fistula in Zhongda Hospital, Southeast University were retrospectively enrolled. Demographics and clinical data were collected. Risk factors selected by univariate analysis for fistula closure were identified by multivariable logistic regression.Results: 288 patients were analyzed in this study of which 94 cases were treated conservatively, 170 cases were treated with an esophageal stent and 24 were treated with a tracheal stent. Among them, the delta Karnofsky's performance status score values (after 2 weeks/before treatment [p=0.0028], after 1 month/before treatment [p=0.0103]) were significantly different between conservative and stent treatment. There was a significant reduction of pneumonia incidence in the stenting group(33.53%) than conservative treatment group(77.05%) after one month(p＜0.0001). In addition, the closure of fistula were influenced by four independent risk factors: 1) treatment methods(p＜ 0.0001), 2) fistula size(p=0.0003), 3) preoperative white blood cell count (p=0.0042), and 4) preoperative Karnofsky's performance status score (p=0.0001).Stent implantation has become an effective method for malignant tracheoesophageal fistula compared to conservative treatment. Besides, stent implantation, smaller size of fistula, lower preoperative white blood cell count, and higher preoperative Karnofsky's performance status score suggest a better outcome.